2020
DOI: 10.1007/s11356-020-10690-7
|View full text |Cite
|
Sign up to set email alerts
|

Single and combined use of Cannabis sativa L. and carbon-rich materials for the removal of pesticides and endocrine-disrupting chemicals from water and soil

Abstract: Hemp (Cannabis sativa L.) seedlings were used to remove from water the fungicide metalaxyl-M and the endocrine disruptor (EDC) bisphenol A (BPA) at concentrations ranging from 2 to 100 μg mL−1. In 7 days of exposure, despite the phytotoxicity of each compound that reduced elongation and biomass, the seedlings were able to remove between 67 and 94% of metalaxyl-M and between 86 and 95% of BPA. The amounts of metalaxyl-M and BPA extracted from plant dry biomass were in the range of 106–3861 μg g−1 and 16–101 μg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Biobased technologies appear to be an interesting economic alternative and easily meet people’s consensus for their nature-friendly approach. Examples of biobased remediation technologies used for the removal of PhEEs and StEEs from environmental matrices are phytoremediation, which uses algae [ 96 ] and higher plants [ 94 ] to absorb and transform organic pollutants, and bioremediation, which uses microorganisms [ 97 , 98 ].…”
Section: Technologies For the Removal Of Estrogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Biobased technologies appear to be an interesting economic alternative and easily meet people’s consensus for their nature-friendly approach. Examples of biobased remediation technologies used for the removal of PhEEs and StEEs from environmental matrices are phytoremediation, which uses algae [ 96 ] and higher plants [ 94 ] to absorb and transform organic pollutants, and bioremediation, which uses microorganisms [ 97 , 98 ].…”
Section: Technologies For the Removal Of Estrogensmentioning
confidence: 99%
“…The addition of BC to soil significantly increases its ability to retain EEs, thus limiting the danger of their leaching to the deeper soil layers and transport to natural waters. This important BC action has been demonstrated in soils naturally or artificially contaminated with BPA [ 90 , 92 , 93 , 94 , 122 ], OP [ 94 ], E1 and E2 [ 123 ] and EE2 [ 92 , 93 ]. Furthermore, the retention of EEs by BC in soil is strongly influenced by the level and type of natural organic matter, in particular the humic fraction, and by dissolved organic matter [ 122 ].…”
Section: Sorptive Removal Of Estrogens By Biosorbentsmentioning
confidence: 99%
“…These hazardous waste can bind to DNA and cause harmful changes in cellular process such as cytotoxicity, carcinogenesis, enzyme function, impaired metabolism and reproductive dysfunctioning [17][18][19] . Several studies have shown that pesticides contamination in soil pose a potential risk to environment and human health [20][21][22] . The lack of information on the fate and potential toxicity of such pollutants make it di cult for regulatory authorities to manage these contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Compost is a more traditional soil amendment with a high content of organic carbon. Its success at reducing the mobility of different types of contaminants has been largely documented in the literature (Loffredo et al 2020;Marín-Benito et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When incorporated in soil, compost and, especially, chars are able to immobilize organic xenobiotics, modulating the amount of these molecules in solution and altering their movement and leaching (Gámiz et al 2016;Loffredo et al 2020). BC demonstrates high efficiency to retain compounds like IMI (Jin et al 2016), BOS (Mukherjee et al 2016), MET (Loffredo et al 2019), OP (Loffredo and Taskin 2017), and BPA (Hurtado et al 2017).…”
Section: Introductionmentioning
confidence: 99%